La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Centre de recherche interuniversitaire sur la littérature et la culture au Québec [CRILCQ], 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Tuning a Room: Designs for Hearing According to Nancy Tobin - Rewa, Natalie (Canadian Theatre Review, 2020)
In this review, I discuss the architectonics of sound composition according to sound artist and designer Nancy Tobin. This chapbook advocates for a comprehensively integrated presence of a sound artist in the processes of rehearsal and espouses a dramaturgy of hearing. Tobin’s distinction between hearing and listening gives forth onto a series of self-studies of her experience of spatial and temporal arrangements presented in the form of e-mails to mentees. Her appreciation for the acoustics of the performance space extends to the composition of sound to be heard (on occasion as boldly interventionist) and the technologies of broadcasting it: the choice and placement of speakers, as well as their interaction with the performers. Tobin argues for a definition of sound composition for performance as a complex collaboration with the production—curatorial in terms of the space of ephemerality. My review concurs with the efficacy of her approach by my recognition of the moments in productions that have remained as some of the most memorable of my theatregoing.
Keywords: Nancy Tobin; acoustic space; rehearsal processes; sonic/acoustic dramaturgy; sound artist; speaker specifications and broadcasting sound